The corporate social responsibility and sustainability in Latin America: Brazil and Mexico. - Lázaro, Lira Luz Benites; Gremaud, Amaury Patrick (Revista de Administração da UFSM, 2015)
Corporate Social Responsibility (CSR) as part of business management in Latin America is a new topic that developed very rapidly in recent decades, driven by globalization, the media and social networks, which demand ethical behavior, respect for human rights and environmental protection from companies. In this context, the paper aims to describe, using the typology proposed by Simon Zadek, the stage in which the CSR issues are situated in two Latin American countries: Brazil and Mexico. The results of the exploratory study showed that the CSR in the two countries are in the stages of emerging and consolidation within the typology about the maturity of the socio-environmental issues in the society.